Primate Visual Perception: Motivated Attention in Naturalistic Scenes - Frank, David W.; Sabatinelli, Dean (Frontiers in Psychology, 2017)
Research has consistently revealed enhanced receptive field activation corresponding to attended cues coupled with suppression to unattended cues. This attention effect depends both on the spatial features of stimuli and internal task goals. However, a large majority of research supporting this effect involves circumscribed tasks that possess few ecologically relevant characteristics. By comparison, natural scenes have the potential to engage an evolved attention system, which may be characterized by features that are distinct from those engaged by reduced experimental paradigms. Here we describe recent animal and human studies of naturalistic scene viewing to highlight the specific impact of social and affective processes on the neural mechanisms of attention modulation.